Symptom Recognition and Healthcare Experiences of Young Women With Acute Myocardial Infarction. (March 2015) - Lichtman, Judith H.; Leifheit-Limson, Erica C.; Watanabe, Emi; Allen, Norrina B.; Garavalia, Brian; Garavalia, Linda S.; Spertus, John A.; Krumholz, Harlan M.; Curry, Leslie A.
Abstract : Background—: Prompt recognition of acute myocardial infarction symptoms and timely care-seeking behavior are critical to optimize acute medical therapies. Relatively little is known about the symptom presentation and care-seeking experiences of women aged ⩽55 years with acute myocardial infarction, a group shown to have increased mortality risk as compared with similarly aged men. Understanding symptom recognition and experiences engaging the healthcare system may provide opportunities to reduce delays and improve acute care for this population. Methods and Results—: We conducted a qualitative study using in-depth interviews with 30 women (aged 30–55 years) hospitalized with acute myocardial infarction to explore their experiences with prodromal symptoms and their decision-making process to seek medical care. Five themes characterized their experiences: (1) prodromal symptoms varied substantially in both nature and duration; (2) they inaccurately assessed personal risk of heart disease and commonly attributed symptoms to noncardiac causes; (3) competing and conflicting priorities influenced decisions about seeking acute care; (4) the healthcare system was not consistently responsive to them, resulting in delays in workup and diagnosis; and (5) they did not routinely access primary care, including preventive care for heart disease. Conclusions—: Participants did not accurately assess their cardiovascular risk, reported poor preventive health behaviors, and delayed seeking care for symptoms, suggesting that differences in both prevention and acute care may be contributing to young women's elevated acute myocardial infarction mortality relative to men. Identifying factors that promote better cardiovascular knowledge, improved preventive health care, and prompt care-seeking behaviors represent important target for this population. Abstract : Supplemental Digital Content is available in the text.